Implikasi Hukum Putusan Mahkamah Agung Nomor 12 P/HUM/2024 terhadap Akuntabilitas Pertanggungjawaban Perjalanan Dinas Dewan Perwakilan Rakyat Daerah - Sipayung, Baren; Rosmini; Andi Wahyudi; Suyanto (Jurnal Kewarganegaraan, 2024)
Abstract The Supreme Court Decision No. 12 P/HUM/2024 has introduced new dynamics in the accountability of travel expenses for members of the Regional House of Representatives (DPRD). This normative legal study thoroughly examines the implications of the decision, particularly the revocation of Presidential Regulation No. 53 of 2023, concerning regional financial accountability and transparency. Through a normative juridical approach and an in-depth literature review of various legal sources—primary, secondary, and tertiary—the study reveals significant changes in the DPRD's travel expense accountability mechanism. The annulment of Presidential Regulation 53/2023 necessitates a shift from the lump-sum system to a reimbursement system based on actual costs (at cost), in accordance with Government Regulation No. 12 of 2019. Furthermore, the decision emphasizes the importance of adherence to fundamental legal principles such as legality, non-retroactivity, and the hierarchy of laws and regulations. Both central and regional governments are urged to promptly adjust their regulations and policies in line with the Supreme Court's decision to ensure accountability and transparency in regional financial management, particularly concerning DPRD travel expenses. This research makes a significant contribution to understanding the impact of the Supreme Court's decision on regional financial governance and provides recommendations for stakeholders to respond to these changes effectively and appropriately. Keywords: Supreme Court Decision; Travel Expenses; DPRD; Accountability; Legal Implications